Multimedia development of basic technique learning for posture and step patterns based on website oriented to Project-Based Learning - Awalinda Safitri; I Gede Suwiwa; I Komang Sukarata Adnyana (Universitas Sriwijaya, 2025)
Research Problems: Mastery of the basic techniques of the ready stance and stepping patterns in martial arts remains a challenge for students due to the limited availability of interactive and accessible learning media. Therefore, it is necessary to develop a web-based multimedia learning tool that integrates a Project-Based Learning approach to enhance students' understanding and skills independently and contextually. Research Objectives: This study aims to develop a web-based multimedia learning product focused on basic techniques of the ready stance and stepping patterns, oriented toward Project-Based Learning, for the course